Ethically Responsible Participant Selection in Research: A Viewpoint. - Irizarry-Pérez, Carlos D.; Fabiano, Leah; Martinez-Fisher, Andrea (Journal of Speech, Language & Hearing Research, 2024)
Purpose: The American Speech-Language-Hearing Association (ASHA) has committed to advancing diversity, equity, and inclusion (DEI) in the profession of speech and hearing sciences. However, there exist significant discrepancies between the demographics of our members and the populations served. These discrepancies extend to the participants included within our research publications. This article addresses participant selection when conducting research investigations. First, we draw attention to standards of conduct that are present within and outside the field. Second, we highlight inequities that exist. We explore a case study as an example. Finally, we offer suggestions to help rectify the problem. Conclusions: Inequities at the level of participants’ selection result in discrepant access to clinical services and evidence-based research for multilingual individuals; neurodiverse individuals; and Black, Indigenous, and people of color communities. ASHA and researchers alike can show commitment to DEI by addressing this problem from multiple approaches.